Antigenic Mimicry in Paraneoplastic Immune Thrombocytopenia - Vial, Guillaume; Rivière, Etienne; Raymond, Anne-Aurélie; James, Chloé; Di-Tommaso, Sylvaine; Dugot-Senant, Nathalie; Dupuy, Jean-William; Yacoub, Mokrane; Parrens, Marie; Saltel, Fréderic; Viallard, Jean-François (Frontiers in Immunology, 2019)
The association of immune thrombocytopenia (ITP) with cancer has been reported, but the causality of tumor cells in paraneoplastic ITP pathogenesis and maintenance has never been established. We analyzed the unusual case of refractory ITP and coincident urothelial tumor of the kidney with circulating high titer anti-GPIIBIIIA autoantibodies. Intriguingly, after nephrectomy, the patient recovered fully and her anti-GPIIBIIIA autoantibodies disappeared. Proteomic and immunohistochemistry analyses revealed erratic GPIIB expression by the tumor cells, suggesting possible antigenic mimicry chronically stimulating the immune system and leading to this patient’s refractory ITP. Such previously unreported findings provide proof-of-concept that requires further confirmation with the prospective study of a larger number of patients.